IMPLEMENTASI LISENSI WAJIB TRIPs AGREEMENT DALAM PRODUK FARMASI DI AMERIKA SERIKAT - Razaq, Dian Fahrinda (Universitas Borneo Tarakan, 2022)
ABSTRACT The TRIPS Agreement provides a comprehensive legal framework to protect andregulate intellectual property rights in the pharmaceutical sector, including in theUnited States, which has implemented this agreement into its national law. Oneimportant aspect of implementing the TRIPS Agreement in the pharmaceutical sector is patent protection. The agreement establishes minimum standards regarding theduration and patent requirements. In this study, a qualitative research method is usedto systematically analyze literature in order to gather and analyze relevant informationregarding compulsory licensing in the TRIPS Agreement. The implementation of theTRIPS Agreement in the US involves various aspects, including the legal system andpharmaceutical regulations, the process of implementation in national laws, and therole of the Food and Drug Administration (FDA) in granting marketing authorizationfor drugs while considering patent protection. Article 31 of the TRIPS Agreement, which pertains to compulsory licensing, plays a crucial role in protecting IPRs in thepharmaceutical sector. This article provides flexibility for TRIPS member countries togrant the use of patents without the patent holder's consent in certain situations thatprotect the public interest. Keywords: Amerika Serikat, Compulsory License, TRIPs Agreement